Environmental, Social and Governance (ESG) - Fuadah, Luk Luk; Mukhtarudin, Mukhtarudin; Andriana, Isni; Arisman, Anton (Integrated Journal of Business and Economics (IJBE), 2023)
This paper presents a Literature review of environmental, social, and governance by browsing several articles that researching the Environmental, Social and Governance (ESG).  This paper reviews 25 papers published between 2021 and 2022.  The stakeholder theory is widely used in research from previous studies on ESG. The 25 papers were published at the Q1 level from Scimagojr.  Most studies conducted their studies by using quantitative methods that mostly used primary data, especially from the Stock Exchange. However, some studies used the qualitative methods. The dominant discussion in these articles is ESG disclosure and also ESG performance. Therefore, future research suggests focusing on topics regarding ESG disclosure or ESG Performance. The next suggestion related to the methods used for future research is a qualitative method, for example, by conducting case studies and direct interviews with sources. The final suggestion for future research that is beneficial to all stakeholders